European countries with a diagnosis of financial default: expectancy and fear of its announcement in Ukraine - Konchyn, V.I. (Економiчний часопис-XXI, 2011)
This paper reviews the economic situation of European countries that today are in deep external debt crisis and
drew close to financial default, that can be announced by the foreign creditors and investors who can not for some
reason get in time or on demand their money (the principal amount provided for use funds and (or) interest on
them). However, in the article the situation of Ukraine’s foreign debt is considered, which significantly increased
as a result of financial management of banks, business entities and due to government and central bank policies
during the Orange epoch. The prospects for economic development in Ukraine are outlined in view of external
debt problem after coming into power the command of the Party of Regions. У статті розглядається економічна ситуація
країн, які сьогодні перебувають у глибокій зовнішній борговій кризі й впритул наблизилися дофінансового дефолту, що оголошується з боку
зовнішніх кредиторів та інвесторів, які не можуть з
певних причин отримати вчасно або за вимогою
свої кошти (основну суму наданих у користування
коштів та (чи) відсотки за користування ними).
Водночас, у статті викладено погляд на ситуацію із
зовнішнім боргом України, що значно збільшився
внаслідок господарювання економічних суб’єктів
та державної політики уряду і НБУ протягом Помаранчевої доби, розкрито перспективи розвитку
економіки з урахуванням проблеми зовнішньої заборгованості країни після приходу до влади команди Партії регіонів. В статье рассматривается экономическая ситуация стран, находящихся сегодня в глубоком
внешнем долговом кризисе и вплотную приблизившихся к финансовому дефолту, который объявляется со стороны внешних кредиторов и инвесторов, не способных по определенным причинам
получить вовремя или по требованию свои средства (основную сумму предоставленных в пользование средств и (или) проценты за пользование
ими). Вместе с тем, в статье изложен взгляд на ситуацию с внешним долгом Украины, который значительно увеличился вследствие хозяйствования
экономических субъектов и проведения государственной политики правительства и НБУ в период
правления Оранжевой власти, раскрыты перспективы развития экономики с учетом проблемы
внешней задолженности страны после прихода к
власти команды Партии регионов.